Expressions of High Status A Comparative Synthesis - Daloz, Jean-Pascal. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book is an unprecedented effort to compare representations and practices of social distinction worldwide and over the centuries. It is based on years of observation in many countries and on the consultation of more than 2 500 multi-disciplinary publications dealing directly or indirectly with this theme. In two previous theoretical volumes on the topic (The Sociology of Elite Distinction and Rethinking Social Distinction) welcomed as major breakthroughs, Jean-Pascal Daloz has established himself as the foremost scholar of symbolic social superiority from a comparative perspective. After having rigorously shown the limits of the main analytical frameworks available and outlined a much more inductive approach, his new empirical book continues this intellectual journey. Taking into consideration all sorts of cases and patterns of meaning, it offers an impressive synthesis demonstrating how diverse the expressions of high status can be. This comparative work is intended to be a crucial reference point and an important source of inspiration for researchers and students across many fields. Jean-Pascal Daloz is a CNRS Research Professor at the University of Strasbourg and Faculty Fellow at the Yale Center for Cultural Sociology. He previously held positions in several universities, including that of Oxford. From 2008-2018, he chaired the International Sociological Association's Research Committee on Comparative Sociology. He has published 16 books so far.
1 Introduction -- Part I External Signs -- 2 Adornments -- 3 Residences -- 4 Vehicles -- 5 Food -- 6 Burials -- Part II Embodied Signs -- 7 Self-Confidence and Assertiveness -- 8 Physical Appearance -- 9 Distinguished Manners -- 10 Cultivation and Linguistic Competence -- Part III Vicarious Display -- 11 Relatives and Glamorous (Fe)male Company -- 12 Flaunting Connections -- 13 Servants -- 14 Artists -- 15 Animals -- Part IV Status-Related Interactions -- 16 Telling Bodily Attitudes -- 17 Precedence -- 18 Gift Exchange -- 19 Conclusion -- Bibliography.
Keywords: Social structure; Equality; Economic sociology; Culture; Sociology; Social Structure; Economic Sociology; Sociology of Culture; Sociological Theory